Low-temperature-resistant lithium-supplementing positive electrode material and preparation method thereof
By using modified lithium square meter in the positive electrode material of lithium-ion batteries, the problem of poor charging and discharging performance of lithium-ion batteries in low temperature environments is solved, and higher electrochemical performance and longer cycle life are achieved.
Patent Information
- Application Number
- CN202510373613.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
Lithium-ion batteries have poor charging and discharging performance in low temperature environments, increase internal resistance, decrease in discharge voltage platform, and reduce charge and discharge capacity, resulting in reduced charge and discharge efficiency and damage to the battery.
A low-temperature lithium supplement positive electrode material is used, which includes lithium supplement agent and modified lithium plaster. Modified lithium platinum is prepared by first loading lithium platinum on graphene activated carbon fibers and then coating a polydopamine layer.
It improves the electrochemical performance of lithium-ion batteries at low temperatures, improves the stability and electrochemical performance of the positive electrode materials at low temperatures, and extends the cycle life of the battery.
Smart Images

Figure H0N324I98FTNC7RZINVCOFM0QMVJ7YJCLW8SBS5F
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a low-temperature resistant lithium-supplementing positive electrode material and a preparation method thereof. Background Art
[0002] In recent years, as lithium-ion batteries have become increasingly mature, their use has become increasingly widespread. However, the environments in which they are used are relatively complex and varied, placing higher demands on their performance. This is particularly true for their charge and discharge performance in low-temperature environments. When charging and discharging batteries at low temperatures, the internal resistance increases, the discharge voltage plateau decreases, the charge and discharge capacity decreases, and the charge and discharge efficiency of the battery is significantly reduced, with some damage to the battery itself. Therefore, improving the electrochemical performance of lithium-ion batteries at low temperatures is a pressing issue. Summary of the Invention
[0003] The object of the present invention is to provide a low-temperature resistant lithium-supplementing cathode material and a preparation method thereof, wherein the low-temperature resistant lithium-supplementing cathode material can improve the problem of poor performance of current batteries at low temperatures.
[0004] In order to achieve the above object, a specific embodiment of the present invention provides the following technical solutions: A low-temperature-resistant lithium-supplementing cathode material comprising a lithium-supplementing agent and modified lithium squarate; The modified lithium squarate is prepared by first loading lithium squarate on graphene activated carbon fibers and then coating them with a polydopamine layer.
[0005] In one or more embodiments of the present invention, in the modified lithium squarate, the mass ratio of lithium squarate to graphene activated carbon fiber is 1:(5-10).
[0006] In one or more embodiments of the present invention, the mass of the modified lithium squarate is 30-40% of the lithium supplement agent.
[0007] In one or more embodiments of the present invention, the lithium supplement is selected from lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate and lithium manganese iron phosphate.
[0008] In one or more embodiments of the present invention, the particle size of the lithium squarate is 300-500 nm, and the diameter of the graphene activated carbon fiber is 3-7 μm and the length is 1-2 mm.
[0009] In one or more embodiments of the present invention, the modified lithium squarate is prepared by dispersing lithium squarate in a solvent, adding graphene activated carbon fibers, impregnating under vacuum, and then drying to obtain a lithium squarate precursor; According to the mass ratio of the lithium squarate precursor to dopamine hydrochloride being (15-20):1, the lithium squarate precursor is added to the dopamine hydrochloride solution, the reaction is followed by centrifugation, and the precipitate is collected and dried to obtain the modified lithium squarate.
[0010] In one or more embodiments of the present invention, the graphene activated carbon fiber is prepared by dispersing graphene in a solvent to form a slurry, then adding a polytetrafluoroethylene solution, mixing well, adding activated carbon fiber and performing ultrasonic treatment, then taking out the activated carbon fiber, calcining, and obtaining the graphene activated carbon fiber.
[0011] In one or more embodiments of the present invention, the mass ratio of the graphene to the activated carbon fiber is 2:(8-10).
[0012] Another specific embodiment of the present invention provides a technical solution as follows: A method for preparing a low-temperature resistant lithium-supplementing cathode material comprises mixing a lithium-supplementing agent and modified lithium squarate to obtain the low-temperature resistant lithium-supplementing cathode material.
[0013] Compared with the existing technology, the present invention first loads lithium squarate on graphene activated carbon fibers, utilizes the low-temperature resistance of graphite and activated carbon fibers to ensure the activity of lithium squarate at low temperatures, and improves the electrochemical performance of the positive electrode material in low-temperature environments. It then coats the material with a polydopamine layer, which can effectively inhibit the adverse effects of the electrolyte on lithium squarate, thereby enabling the battery to maintain stable electrochemical performance at low temperatures. DETAILED DESCRIPTION
[0014] To help those skilled in the art better understand the technical solutions of the present invention, the following clearly and completely describes the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work should fall within the scope of protection of the present invention.
[0015] A specific embodiment of the present invention provides a low-temperature resistant lithium-supplementing positive electrode material, comprising a lithium-supplementing agent and modified lithium squarate, wherein the modified lithium squarate is prepared by first loading lithium squarate on graphene activated carbon fibers and then coating the graphene activated carbon fibers with a polydopamine layer.
[0016] Specifically, first, carbon fiber can improve the stability and energy density of the battery in the positive electrode material. Secondly, carbon fiber has excellent low-temperature resistance and can maintain structural stability in a relatively low temperature environment. In addition, graphene not only has good low-temperature resistance, but also has excellent conductivity, which can improve the charge and discharge efficiency and power performance of the battery. The present invention first composites graphene with carbon fiber, then utilizes the high specific area of graphene to load lithium squarate, and finally coats it with a polydopamine layer to suppress the negative impact of the electrolyte on lithium squarate, thereby improving the stability of the modified lithium squarate at low temperatures. At the same time, in combination with a lithium supplement, the cycle life of the battery is further improved, ultimately achieving the purpose of improving the electrochemical performance of the battery in a low-temperature environment.
[0017] Furthermore, in the modified lithium squarate, the mass ratio of lithium squarate to graphene activated carbon fiber is 1:(5-10), the particle size of lithium squarate is 300-500nm, the diameter of graphene activated carbon fiber is 3-7μm, and the length is 1-2m.
[0018] Specifically, graphene activated carbon fibers not only have a high specific surface area, but also have abundant pores. In the modified lithium squarate, lithium squarate is not only filled in the pores of the graphene activated carbon fibers, but also loaded on the surface of the graphene activated carbon fibers. By controlling the mass ratio and specifications between lithium squarate and graphene activated carbon fibers, it is beneficial for lithium squarate to be loaded in both the pores and the surface of the graphene activated carbon fibers, thereby better improving the electrochemical performance of the battery in a low-temperature environment.
[0019] Furthermore, the preparation of modified quartz crystal is as follows: first, graphene is dispersed in a solvent to form a slurry, and then a polytetrafluoroethylene solution is added. After mixing, activated carbon fibers are added according to a mass ratio of graphene to activated carbon fibers of 2: (8-10) and ultrasonic treatment is performed. Then, the activated carbon fibers are removed and calcined to obtain graphene activated carbon fibers; lithium quartz crystal is dispersed in a solvent according to a mass ratio of lithium quartz crystal to graphene activated carbon fibers of 1: (5-10), and then graphene activated carbon fibers are added, impregnated under vacuum, and then dried to obtain a lithium quartz crystal precursor; lithium quartz crystal precursor is added to a dopamine hydrochloride solution according to a mass ratio of lithium quartz crystal precursor to dopamine hydrochloride of (15-20): 1, centrifuged after reaction, and the precipitate is taken and dried to obtain modified quartz crystal. By controlling the amount of raw materials, lithium quartz crystal can be evenly loaded on the graphene activated carbon fibers, and the polydopamine layer can evenly cover the lithium quartz crystal precursor, effectively maintaining the performance of the modified lithium quartz crystal at low temperatures.
[0020] Furthermore, the mass of the modified lithium squarate is 30-40% of the lithium supplement agent.
[0021] Specifically, the lithium supplement is selected from lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate and lithium manganese iron phosphate. The above types of lithium supplements have good cycle stability, stable structure and high safety, which help to ensure the stability of the electrochemical performance of the battery at low temperatures.
[0022] Another specific embodiment of the present invention provides a method for preparing a low-temperature resistant lithium-supplementing positive electrode material, comprising uniformly mixing modified lithium squarate and a lithium-supplementing agent according to a proportion.
[0023] Specifically, the advantages of using modified lithium squarate to prepare low-temperature resistant lithium-supplementing positive electrode materials are: graphene activated carbon fibers give the positive electrode materials good low-temperature resistance and conductivity, and loading lithium squarate on graphene activated carbon fibers can effectively improve the electrochemical performance of the positive electrode materials at low temperatures; dopamine hydrochloride can form a polydopamine layer on the lithium squarate precursor by self-polymerization, and the polydopamine layer can inhibit the negative impact of the electrolyte on the positive electrode material. At the same time, the polydopamine layer contains a microporous structure for lithium ion transmission, which can ensure that the positive electrode material effectively exerts its electrochemical properties.
[0024] The present invention is further described in detail below in conjunction with specific implementations.
[0025] The graphene in the present invention is graphene oxide, purchased from Aladdin Chemical; the polytetrafluoroethylene solution was purchased from Shanghai Fengguang Plastics; and the activated carbon fiber was purchased from Dongguan Wanlixiang Carbon Fiber.
[0026] Preparation Example of Modified Lithium Squarate Preparation Example 1 25g of graphene and 90g of sodium bicarbonate were added to 10L of anhydrous ethanol, and a slurry was prepared after ultrasonic treatment. Under ultrasonication, 90g of a 60wt% polytetrafluoroethylene solution was added to the slurry, followed by 100g of activated carbon fibers with a diameter of 3-7μm and a length of 1-2mm. The slurry was ultrasonicated for 1.5 hours. After ultrasonication, the hollow activated carbon fibers were removed and calcined at 380°C for 10 minutes to obtain graphene-activated carbon fibers.
[0027] According to the mass ratio of squaric acid powder to water of 2:100, squaric acid powder was dissolved in water to prepare squaric acid solution. + :Lithium source (Li + ) with a molar ratio of 1:1.15. Lithium carbonate was weighed and added to the squaric acid solution. The reaction was carried out at 60°C for 3.1 hours, and then vacuum dried at 60°C. The solution was washed with ethanol and then dried to obtain lithium squarate. The particle size of the lithium squarate was in the range of 300-500 nm.
[0028] Lithium squarate and graphene activated carbon fibers were taken separately according to a mass ratio of lithium squarate to graphene activated carbon fibers of 1:5, lithium squarate was dispersed in N-methyl-2-pyrrolidone, and then graphene activated carbon fibers were added, impregnated under a vacuum environment for 10 minutes, and then dried at 80°C to obtain a lithium squarate precursor.
[0029] Prepare tris(hydroxymethyl)aminomethane hydrochloride buffer solution and adjust the pH to 8.5 with hydrochloric acid. Add 60 g of lithium squarate precursor and 4 g of dopamine hydrochloride into 1.5 L of buffer solution and react for 1 h. After the reaction, dry to obtain modified lithium squarate.
[0030] Preparation Example 2 25g of graphene and 90g of sodium bicarbonate were added to 10L of anhydrous ethanol, and the mixture was ultrasonically treated to form a slurry. Under ultrasonication, 90g of a 60wt% aqueous solution of polytetrafluoroethylene was added to the slurry, followed by 125g of hollow activated carbon fibers with a diameter of 3-7μm and a length of 1-2mm. The mixture was ultrasonicated for 1.5h. After ultrasonication, the hollow activated carbon fibers were removed and calcined at 380°C for 10min to obtain graphene activated carbon fibers.
[0031] According to the mass ratio of squaric acid powder to water of 2:100, squaric acid powder was dissolved in water to prepare squaric acid solution. + :Lithium source (Li + ) with a molar ratio of 1:1.15. Lithium carbonate was weighed and added to the squaric acid solution. The reaction was carried out at 60°C for 3.1 hours, and then vacuum dried at 60°C. The solution was washed with ethanol and then dried to obtain lithium squarate. The particle size of the lithium squarate was in the range of 300-500 nm.
[0032] Lithium squarate and graphene activated carbon fibers were taken separately according to a mass ratio of lithium squarate to graphene activated carbon fibers of 1:8, the lithium squarate was dispersed in N-methyl-2-pyrrolidone, and then the graphene activated carbon fibers were added, impregnated under a vacuum environment for 10 minutes, and then dried at 80°C to obtain a lithium squarate precursor.
[0033] Prepare tris(hydroxymethyl)aminomethane hydrochloride buffer solution and adjust the pH to 8.5 with hydrochloric acid. Add 80 g of lithium squarate precursor and 4 g of dopamine hydrochloride into 1.5 L of buffer solution and react for 1 h. After the reaction, dry to obtain modified lithium squarate.
[0034] Preparation Example 3 Take 10L of anhydrous ethanol, add 25g of graphene and 90g of sodium bicarbonate, and ultrasonicate to make a slurry. Under ultrasonication, add 90g of a 60wt% polytetrafluoroethylene aqueous solution to the slurry, then add 100g of hollow activated carbon fibers with a diameter of 3-7μm and a length of 1-2mm, and ultrasonicate for 1.5 hours. After ultrasonication, remove the hollow activated carbon fibers and calcine them at 380℃ for 10 minutes to obtain graphene activated carbon fibers.
[0035] According to the mass ratio of squaric acid powder to water of 2:100, squaric acid powder was dissolved in water to prepare squaric acid solution. + :Lithium source (Li + ) with a molar ratio of 1:1.15. Lithium carbonate was weighed and added to the squaric acid solution. The reaction was carried out at 60°C for 3.1 hours, and then vacuum dried at 60°C. The solution was washed with ethanol and then dried to obtain lithium squarate. The particle size of the lithium squarate was in the range of 300-500 nm.
[0036] Lithium squarate and graphene activated carbon fibers were taken separately according to a mass ratio of lithium squarate to graphene activated carbon fibers of 1:10, lithium squarate was dispersed in N-methyl-2-pyrrolidone, and then graphene activated carbon fibers were added, impregnated under vacuum for 10 minutes, and then dried at 80°C to obtain a lithium squarate precursor.
[0037] A tris(hydroxymethyl)aminomethane hydrochloride buffer solution was prepared and the pH was adjusted to 8.5 with hydrochloric acid. 68 g of a lithium squarate precursor and 4 g of dopamine hydrochloride were added to 1.5 L of the buffer solution for reaction for 1 h. After the reaction, the solution was dried to obtain a modified lithium squarate.
[0038] Preparation Example 4 The only difference between this preparation example and preparation example 1 is that the mass ratio of lithium squarate to graphene activated carbon fiber is 1:20.
[0039] Preparation Example 5 The only difference between this preparation example and preparation example 1 is that tris(hydroxymethyl)aminomethane hydrochloride buffer solution is prepared and the pH is adjusted to 8.5 with hydrochloric acid, 100 g of lithium squarate precursor and 4 g of dopamine hydrochloride are added to 1.5 L of buffer solution and reacted for 1 hour. After the reaction, the solution is dried to obtain modified lithium squarate.
[0040] Examples of low-temperature-resistant lithium-supplementing positive electrode materials Example 1 Take the modified lithium squarate and lithium manganate in Preparation Example 1, mix the two according to the ratio of the mass of the modified lithium squarate to the mass of the lithium manganate, and stir at a speed of 600 r / min for 30 minutes to obtain a low-temperature resistant lithium-supplementing positive electrode material.
[0041] Example 2 Take the modified lithium squarate and lithium manganate in Preparation Example 1, mix the two according to the ratio of the mass of the modified lithium squarate to the mass of the lithium manganate, and stir at a speed of 600 r / min for 30 minutes to obtain a low-temperature resistant lithium-supplementing positive electrode material.
[0042] Example 3 Take the modified lithium squarate and lithium manganate in Preparation Example 1, mix the two according to the ratio of the mass of the modified lithium squarate to the mass of the lithium manganate, and stir at a speed of 600 r / min for 30 minutes to obtain a low-temperature resistant lithium-supplementing positive electrode material.
[0043] Example 4 Take the modified lithium squarate and lithium manganate in Preparation Example 2, mix the two according to the ratio of the mass of the modified lithium squarate to the mass of the lithium manganate, and stir at a speed of 600 r / min for 30 minutes to obtain a low-temperature resistant lithium-supplementing positive electrode material.
[0044] Example 5 Take the modified lithium squarate and lithium manganate in Preparation Example 3, mix the two according to the ratio of the mass of the modified lithium squarate to the mass of the lithium manganate, and stir at a speed of 600 r / min for 30 minutes to obtain a low-temperature resistant lithium-supplementing positive electrode material.
[0045] Example 6 Take the modified lithium squarate and lithium manganate in Preparation Example 4, mix the two according to the ratio of the mass of the modified lithium squarate to the mass of the lithium manganate, and stir at a speed of 600 r / min for 30 minutes to obtain a low-temperature resistant lithium-supplementing positive electrode material.
[0046] Example 7 Take the modified lithium squarate and lithium manganate in Preparation Example 5, mix the two according to the ratio of the mass of the modified lithium squarate to the mass of the lithium manganate, and stir at a speed of 600 r / min for 30 minutes to obtain a low-temperature resistant lithium-supplementing positive electrode material.
[0047] Comparative Example 1 25g of graphene and 90g of sodium bicarbonate were added to 10L of anhydrous ethanol, followed by sonication to form a slurry. Under sonication, 90g of a 60wt% aqueous solution of polytetrafluoroethylene was added to the slurry, followed by 100g of activated carbon fibers, and sonication was continued for 1.5h. After sonication, the activated carbon fibers were removed and calcined at 380°C for 10min to obtain graphene-based activated carbon fibers.
[0048] According to the mass ratio of squaric acid powder to water of 2:100, squaric acid powder was dissolved in water to prepare squaric acid solution. + :Lithium source (Li + ) with a molar ratio of 1:1.15. Lithium carbonate was weighed and added to the squaric acid solution. The mixture was reacted at 60°C for 3.1 hours, and then vacuum dried at 60°C. The mixture was washed with ethanol and then dried to obtain lithium squarate.
[0049] The three were mixed according to the ratio of the mass of lithium squarate to the mass of lithium manganate, the mass of graphene activated carbon fiber to the mass of lithium manganate to the mass of lithium manganate, and stirred at a speed of 600 r / min for 30 minutes to obtain a lithium-supplemented positive electrode material.
[0050] Comparative Example 2 25g of graphene and 90g of sodium bicarbonate were added to 10L of anhydrous ethanol, followed by sonication to form a slurry. Under sonication, 90g of a 60wt% aqueous solution of polytetrafluoroethylene was added to the slurry, followed by 100g of activated carbon fibers, and sonication was continued for 1.5h. After sonication, the activated carbon fibers were removed and calcined at 380°C for 10min to obtain graphene-based activated carbon fibers.
[0051] According to the mass ratio of squaric acid powder to water of 2:100, squaric acid powder was dissolved in water to prepare squaric acid solution. + :Lithium source (Li + ) with a molar ratio of 1:1.15. Lithium carbonate was weighed and added to the squaric acid solution. The mixture was reacted at 60°C for 3.1 hours, and then vacuum dried at 60°C. The mixture was washed with ethanol and then dried to obtain lithium squarate.
[0052] Lithium squarate and graphene activated carbon fibers were taken separately according to a mass ratio of lithium squarate to graphene activated carbon fibers of 1:5, the lithium squarate was dispersed in N-methyl-2-pyrrolidone, and then the graphene activated carbon fibers were added, impregnated under a vacuum environment for 10 minutes, and then dried at 80°C to obtain modified lithium squarate.
[0053] The modified lithium squarate is 30% of the lithium manganate in mass, and the two are mixed and stirred at a speed of 600 r / min for 30 minutes to obtain a lithium-supplemented positive electrode material.
[0054] The performance tests were conducted on the lithium-supplemented positive electrode materials in each embodiment and each comparative example, as follows: The lithium-supplemented cathode material, conductive carbon black, and PVDF were added to N-methyl-2-pyrrolidone at a mass ratio of 8:1:1. The mixture was mixed to form a slurry, which was evenly coated onto aluminum foil and dried in an 80°C oven to produce a positive electrode sheet. The positive electrode sheet was assembled into a coin cell battery with an electrolyte of 1 mol / L LiPF6 (EC:DMC = 1:1) and a lithium sheet as the negative electrode. The battery was charged at room temperature at a current of 0.5C and then discharged at 0.2C to 2.5V after 5 minutes. The capacity was recorded and designated as Capacity 1. After charging at 0.5C again, the battery was placed at -20°C and -30°C, respectively, and discharged at 0.2C. The capacity at -20°C was designated as Capacity 2, and the capacity at -30°C was designated as Capacity 3. The capacity retention ratio at -20°C was Capacity 2 / Capacity 1 × 100%, and the capacity retention ratio at -30°C was Capacity 3 / Capacity 1 × 100%.
[0055] Table 1 Electrochemical test results Compared with Comparative Example 1 and Comparative Example 2, the low-temperature resistant lithium-supplementing positive electrode material in the embodiment of the present invention has a higher low-temperature discharge capacity retention rate and exhibits better low-temperature resistance, indicating that the present invention first loads lithium squarate on graphene activated carbon fiber and then coats it with polydopamine, which can effectively improve the electrochemical performance of the battery at low temperatures.
[0056] In addition, comparing Example 1, Example 6 and Example 7, the low-temperature discharge capacity retention rate of the low-temperature resistant lithium-replenishing positive electrode material in Example 6 and Example 7 is slightly lower than that in Example 1, indicating that the low-temperature resistant lithium-replenishing positive electrode material is prepared according to the ratio disclosed in this application, which can ensure that the low-temperature resistant lithium-replenishing positive electrode material has better electrochemical properties and meets the performance requirements of the battery at low temperatures.
[0057] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention. In addition, it should be understood that although this specification is described in terms of implementation methods, not each implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in the various embodiments can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
Claims
1. A low temperature resistant lithium supplementing positive electrode material, characterized in that: Including lithium supplements and modified lithium squarate; The modified lithium squarate is prepared by first loading lithium squarate on graphene activated carbon fibers and then coating them with a polydopamine layer.
2. The low temperature resistant lithium supplementing positive electrode material according to claim 1, characterized in that: In the modified lithium squarate, the mass ratio of lithium squarate to graphene activated carbon fiber is 1:(5-10).
3. The low temperature resistant lithium supplementing positive electrode material according to claim 1, characterized in that: The mass of the modified lithium squarate is 30-40% of the lithium supplement agent.
4. The low temperature resistant lithium supplementing positive electrode material according to claim 1, characterized in that: The lithium supplement is selected from lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate and lithium manganese iron phosphate.
5. The low temperature resistant lithium supplementing positive electrode material according to claim 1, characterized in that: The particle size of the lithium squarate is 300-500nm, the diameter of the graphene activated carbon fiber is 3-7μm, and the length is 1-2mm.
6. The low temperature resistant lithium supplementing positive electrode material according to claim 1, characterized in that: The modified lithium squarate is prepared by dispersing lithium squarate in a solvent, adding graphene activated carbon fiber, impregnating under vacuum, and then drying to obtain a lithium squarate precursor; According to the mass ratio of the lithium squarate precursor to dopamine hydrochloride of (15-20):1, the lithium squarate precursor is added to the dopamine hydrochloride solution, centrifuged after the reaction, and the precipitate is taken and dried to obtain the modified lithium squarate.
7. The low temperature resistant lithium supplementing positive electrode material according to claim 6, characterized in that: The graphene activated carbon fiber is prepared by dispersing graphene in a solvent to prepare a slurry, adding a polytetrafluoroethylene solution, mixing well, adding activated carbon fiber and performing ultrasonic treatment, then taking out the activated carbon fiber and calcining to obtain the graphene activated carbon fiber.
8. The low temperature resistant lithium supplementing positive electrode material according to claim 7, characterized in that: The mass ratio of the graphene to the activated carbon fiber is 2:(8-10).
9. The method for preparing the low temperature resistant lithium supplementing positive electrode material according to any one of claims 1 to 8, characterized in that: The lithium replenishing agent and the modified lithium squarate are mixed evenly to obtain a low-temperature resistant lithium replenishing positive electrode material.
Citation Information
Patent Citations
Conversion type negative electrode material structure design and preparation method for lithium ion battery
CN116154139A
Positive electrode lithium supplementing material and preparation method and application thereof
CN116598443A
Composite lithium supplementing material and preparation method and application thereof
CN117099227A
Composite lithium supplementing material and preparation method thereof, positive electrode material and secondary battery
CN118213641A
Composite lithium supplementing material, preparation method thereof and battery
CN118299578A